Facing up to issues - Razak, Dzulkifli Abd (2011)
I WOULD like to thank Ariff Shah R. K. for his letter to the editor (New Straits Times, Feb 11) on matters of the "Paraiyars" that have been causing much anxiety recently. I appreciate his thoughts and viewpoints -- which at the end of it all -- do not differ much from what I wrote in my Feb 6 column. Ariff seemed to concur that the Paraiyars "were indeed once landowners who lost their land, advisers to the kings, farmers, musicians, singers and members of the manual workforce" and directed the cause to the divide-and-rule policy of the British.